Metal monatomic supported sodium ion battery negative electrode material and preparation method thereof
By modifying the biomass carbon source metal single atoms, the structure of hard carbon materials is optimized, and the problem of insufficient performance of hard carbon anode materials in sodium ion batteries is solved, thereby achieving efficient performance improvement of sodium ion batteries and simplifying the preparation process.
Patent Information
- Application Number
- CN202411330574.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The existing hard carbon anode material has low efficiency in the first week of sodium ion batteries, poor discharge rate, low reversible capacity, and complex preparation process, making it difficult to meet the needs of improved performance of sodium batteries.
By calcining the biomass carbon source with a non-metal doping source, immersing the high-concentration metal salt solution and rinsing it with acid, we construct a hard carbon material modified by metal single atoms, optimizing the graphite nanodomain layer spacing and defect structure, and reducing sodium The ion diffusion kinetic energy barrier forms a thin and efficient SEI film.
The first week of the sodium ion battery has been significantly improved, the long cycle stability and discharge rate of the sodium ion battery has been achieved. The capacity of the sodium ion battery reaches 342mAh/g, the first week of the Coulomb efficiency reaches 91.2%, the capacity retention rate of 200 weeks exceeds 95%, and the preparation is simplified. Craft.
Smart Images

Figure CN119143111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery negative electrode material carrying a metal single atom and a preparation method thereof, belonging to the technical field of chemical power sources. Background Art
[0002] Under the current "dual carbon" background, the overall energy structure of society has undergone great changes. Among various storage media, new chemical energy storage media play an increasingly important role. Among them, sodium-ion batteries have attracted widespread attention due to their advantages of low cost, wide temperature range and high safety. Graphite anodes are often difficult to apply to sodium-ion battery anode materials due to their low first-week coulombic efficiency, poor discharge rate, and low reversible capacity. In order to solve this technical problem, the industry replaced graphite anode materials with hard carbon materials; compared with graphite anodes, hard carbon anode materials have the characteristics of large interplanar spacing, rich defect sites, and excellent sodium storage performance. During the charging process, sodium ions are adsorbed and deposited on the defect sites or vacancies of carbon materials. As the charging process continues, sodium ions are intercalated into the graphite interlayers. Therefore, the defect structure, concentration, pore structure and interlayer spacing of graphite domains of hard carbon materials have an important influence on the sodium storage performance of hard carbon materials. In order to improve the sodium storage performance of hard carbon materials, engineers have optimized the performance of hard carbon materials from multiple aspects such as pore structure control, defect control, atomic doping, and graphite nanodomain structure. However, the effect on the performance improvement of hard carbon negative electrode materials is still very limited, and there are often technical problems such as harsh preparation technology and complex preparation process. Developing a simple and mild hard carbon negative electrode material preparation process to improve the performance of hard carbon negative electrode materials and help sodium batteries achieve higher first-week coulomb efficiency, higher discharge rate and greater reversible capacity has become a technical problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom to solve the above technical problems.
[0004] The technical solution to achieve the purpose of the present invention is: a method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom, characterized by comprising the following steps:
[0005] S1: calcining the biomass carbon source under an inert atmosphere to obtain a hard carbon material;
[0006] S2: crushing the hard carbon material in the previous step and grinding it with a non-metallic doping source to obtain a precursor-containing mixture;
[0007] S3: sintering the precursor-containing mixture under an inert atmosphere to obtain a hard carbon material doped with non-metallic heteroatoms;
[0008] S4: impregnating the non-metallic heteroatom-doped hard carbon material in a high-concentration metal salt solution, centrifugally drying, and then sintering in an inert atmosphere to obtain a sintered product;
[0009] S5: The sintered product obtained in the above step is washed with an acid aqueous solution.
[0010] The present invention effectively increases the interlayer spacing of graphite nanodomains, optimizes the functional group structure and concentration of defects, and reduces the diffusion kinetic energy barrier of sodium ions in hard carbon materials by performing step-by-step single-atom point modification on the preliminarily synthesized biomass carbon source hard carbon material. It has been tested that it can effectively construct a thin and efficient SEI film, which can effectively improve the first-week coulomb efficiency, long-cycle stability and discharge rate of sodium ion batteries when applied to sodium ion batteries. According to tests, the sodium ion battery capacity of a sodium ion battery negative electrode material loaded with metal single atoms prepared by the present invention can reach up to 342mAh / g, the first-week coulomb efficiency reaches 91.2%, and the capacity retention rate of 200 weeks of 0.1C charge and discharge exceeds 95%.
[0011] The preparation method of the present invention is very simple and has excellent effect, which is very helpful to promote the large-scale commercial promotion of sodium ion batteries.
[0012] Further or optionally, the calcination temperature in step S1 is 1000-1500°C, and the calcination time is 2-10 hours. The sintering temperature and sintering time are adjusted as needed during the specific preparation process. The particle size, defect structure, and hierarchical pore structure (including micropores, mesopores, and macropores) of the hard carbon material are key factors affecting subsequent modification.
[0013] Further or optionally, the non-metal doped into the non-metallic doping source is nitrogen, phosphorus or sulfur, and the non-metallic doping source is one or more of urea, dicyandiamide, melamine, dopamine hydrochloride, thiourea, polyaniline, polypropylamine, polypyridine, polypyrrole, chitosan, sodium hypophosphite, sodium hypophosphite, ammonium dihydrogen phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, sodium sulfide nonahydrate, sublimated sulfur, and sodium dodecyl sulfate, and the specific type is selected according to needs.
[0014] Further or optionally, in the doping process of step S2, the material ratio of the hard carbon material to the non-metallic doping source is C:(N / P / S)=100:1~100:25. This ratio will affect the optimization result of the defect structure in the hard carbon material and provide a chemical microenvironment for the subsequent anchoring of metal single atoms.
[0015] Further or optionally, in step S3, the sintering temperature is 300-800° C., and the sintering time is 0.5-5 hours. The sintering temperature affects the content of the doped non-metallic elements, so the temperature and time of the high-temperature treatment need to be strictly controlled.
[0016] Further or optionally, the high concentration metal salt solution in step S4 is zinc nitrate, zinc chloride, zinc acetate, zinc sulfate, cupric chloride, copper nitrate, copper sulfate, copper acetate, ferric chloride, ferric nitrate, potassium ferrocyanide, nickel chloride, nickel sulfate, cobalt nitrate, cobalt chloride, manganese chloride, manganese acetate, ammonium molybdate, sodium tungstate, ammonium metatungstate, vanadium trichloride, cadmium chloride, cadmium nitrate, chromium chloride, ammonium cerium nitrate, cerium nitrate, magnesium carbonate, magnesium chloride, magnesium acetate, calcium chloride, calcium sulfate, calcium carbonate, aluminum chloride, zirconium chloride or a mixture thereof, and its concentration range is 1 to 10 mol / L. During the experimental stage, parameter tests are performed on each salt solution, and the data are recorded and classified and the dosage is calculated according to the main metal types.
[0017] Further or optionally, the sintering temperature in step S4 is 300-1000°C, and the processing time is optional: 0.5-3 hours. The sintering temperature and sintering time have a significant impact on the metal salt doping effect, and the sintering temperature, sintering time and sintering atmosphere need to be strictly controlled. The hard carbon material carrying metal single atoms can effectively reduce the diffusion kinetic energy barrier of sodium atoms between layers, which is conducive to building a thin and efficient SEI film and accelerating the filling and embedding process of sodium ions.
[0018] Further or optionally, the acid used for rinsing in step S5 is hydrochloric acid, sulfuric acid, acetic acid or a mixture thereof, and the pH value thereof is controlled to be 0.1-1.
[0019] The present invention also provides a sodium ion battery negative electrode material, which is prepared by the above method.
[0020] By adopting the above technical solution, the present invention has the following beneficial effects:
[0021] (1) The present invention effectively increases the interlayer spacing of graphite nanodomains, optimizes the functional group structure and concentration of defects, and reduces the diffusion kinetic energy barrier of sodium ions in hard carbon materials by performing step-by-step single-atom point modification on the preliminarily synthesized biomass carbon source hard carbon material. It has been tested that it can effectively construct a thin and efficient SEI film, and when applied to sodium ion batteries, it can effectively improve the first-week coulomb efficiency, long-cycle stability and discharge rate of sodium ion batteries. According to tests, the sodium ion battery capacity of a sodium ion battery negative electrode material loaded with metal single atoms prepared by the present invention can reach up to 342mAh / g, the first-week coulomb efficiency reaches 91.2%, and the capacity retention rate of 0.1C charge and discharge for 200 weeks exceeds 95%. The preparation method of the present invention is very simple and has excellent effects, which is very conducive to promoting the large-scale commercial promotion of sodium ion batteries.
[0022] (2) The present invention strictly controls the calcination temperature and calcination time during the preparation process of the negative electrode material for sodium ion batteries, and the specific surface area, particle size, defect structure, pore structure, etc. of the product can be strictly controlled, and the overall distribution is relatively uniform.
[0023] (3) The present invention strictly optimizes the type and doping ratio of non-metallic doping sources, thereby achieving the decoration and regulation of the functional group structure of defect sites in hard carbon materials. At the same time, heteroatom doping is performed on the surface of hard carbon materials to create defect sites, thereby ensuring that metal single atoms can be stably anchored in the hard carbon materials.
[0024] (4) The present invention optimizes the type and concentration of metal single atoms used to modify the hard carbon material, which can effectively change the surface microenvironment of the hard carbon material. The product has good stability and excellent sodium storage capacity and potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments and in conjunction with the accompanying drawings, wherein
[0026] Figure 1 This is a spherical aberration corrected transmission electron microscope image of Example 1;
[0027] Figure 2 This is the XRD spectrum of the hard carbon material supporting metal single atoms of Example 1;
[0028] Figure 3 is a curve diagram of the first charge and discharge of Example 1;
[0029] Figure 4 It is the 0.1C charge and discharge capacity retention rate of Example 1. DETAILED DESCRIPTION
[0030] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0032] All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work shall fall within the protection scope of the present invention.
[0033] (Example 1)
[0034] The coconut shell was dried at 100 ° C for 5 hours, crushed and placed in an inert gas-protected muffle furnace, heated to 1000 ° C at a heating rate of 20 ° C per minute, and kept warm for 2 hours for high temperature treatment. After high temperature treatment, it was cooled and air flow crushed to a median particle size of 5 ± 0.5 μm. A certain amount of coconut shell-derived hard carbon was ground and mixed with an appropriate amount of urea in a mass ratio of 10:1. The mixture was placed in an inert gas-protected muffle furnace, heated to 800 ° C at a heating rate of 10 ° C per minute, kept warm for 1 hour, and naturally cooled to room temperature to obtain nitrogen-doped hard carbon material. The nitrogen-doped hard carbon material was ground and dispersed in 500 mL of a 5M magnesium chloride aqueous solution. After ultrasonication and stirring overnight, the precipitate was centrifuged and removed. After drying at 60 ° C for 12 hours, it was placed in an inert gas-protected muffle furnace, heated to 800 ° C at a heating rate of 10 ° C per minute, kept warm for 1 hour, and then naturally cooled. After grinding and passing through a 500-mesh sieve, the final magnesium single atom modified hard carbon material is obtained.
[0035] The characterization results of the spherical aberration-corrected transmission electron microscope of the magnesium single atom modified hard carbon material obtained in this example are as follows: Figure 1 As shown in the high-angle annular dark field image mode, the Mg metal can be distinguished by the thickness contrast to exist in the form of a single atom on the hard carbon material substrate. Figure 2 As shown in Figure 2, the presence of the bulge peak indicates its poor crystallinity. The interplanar spacing of the graphite-like structure can be deduced from the Bragg equation:
[0036] Button cell production: Sodium sheet is used as the counter electrode, 1 mol / L NaPF6 / DIGLYME (100 Vol%) is used as the electrolyte, glass fiber is used as the separator, and 2032 button cell shell is used to assemble a button half cell. The first charge and discharge curve results are shown in the figure below. Figure 3 The capacity retention rate of 200 cycles of 0.1C charge and discharge is shown in Figure 4 The battery performance characterization results are shown in Table 2.
[0037] (Example 2)
[0038] The walnut shell was dried at 100 ° C for 1 hour, crushed and placed in an inert gas-protected muffle furnace, heated to 1500 ° C at a heating rate of 20 ° C per minute, and kept warm for 5 hours for high temperature treatment. After high temperature treatment, it was cooled and ball milled to a median particle size of 1 ± 0.5 μm. A certain amount of walnut shell-derived hard carbon was ground and mixed with an appropriate amount of thiourea and potassium dihydrogen phosphate in a mass ratio of 10:2:1. The mixture was placed in an inert gas-protected muffle furnace, heated to 450 ° C at a heating rate of 10 ° C per minute, kept warm for 1.5 hours, and naturally cooled to room temperature to obtain nitrogen, phosphorus and sulfur co-doped hard carbon material. The nitrogen, phosphorus and sulfur co-doped hard carbon material was ground and dispersed in 500 mL of 1M ferric chloride aqueous solution. After ultrasonication and stirring overnight, the precipitate was washed and centrifuged. After drying at 60°C for 12 hours, the material was placed in an inert gas-protected muffle furnace and heated to 900°C at a rate of 10°C per minute, kept at that temperature for 1 hour, and then cooled naturally. After grinding and passing through a 500-mesh sieve, the final iron single atom-modified hard carbon material was obtained.
[0039] The hard carbon material in Example 1 was replaced by the hard carbon material in this example, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.
[0040] (Example 3)
[0041] An appropriate amount of starch-based precursor material is placed in an inert gas-protected muffle furnace, heated to 500°C at a heating rate of 20°C per minute, and then cooled naturally to room temperature after 3 hours of heat preservation. The product is ball-milled until D90 is less than 10±0.5μm. The ground powder is placed in an inert gas-protected muffle furnace again, heated to 1300°C at a heating rate of 20°C per minute, and then cooled naturally to room temperature after 2 hours of heat preservation to obtain a starch-based hard carbon material. A certain amount of starch-based hard carbon is ground and mixed with an appropriate amount of ammonium monohydrogen phosphate in a mass ratio of 10:4. The mixture is placed in an inert gas-protected muffle furnace, heated to 600°C at a heating rate of 10°C per minute, kept warm for 5 hours, and naturally cooled to room temperature to obtain a nitrogen-phosphorus dual-doped hard carbon material. After grinding the taken-out nitrogen-phosphorus dual-doped hard carbon material, it is dispersed in 500mL of a 5M zinc nitrate aqueous solution. After ultrasonication and stirring overnight, the precipitate is washed and centrifuged to remove. After drying at 60°C for 12 hours, the material was placed in an inert gas-protected muffle furnace and heated to 1000°C at a rate of 10°C per minute, kept at that temperature for 3 hours, and then cooled naturally. After grinding and passing through a 500-mesh sieve, the final zinc single atom-modified hard carbon material was obtained.
[0042] The hard carbon material in Example 1 was replaced by the hard carbon material in this example, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.
[0043] (Example 4)
[0044] The walnut shell was dried at 100 ° C for 1 hour, crushed and placed in an inert gas-protected muffle furnace, heated to 1400 ° C at a heating rate of 20 ° C per minute, and kept warm for 3 hours for high temperature treatment. After high temperature treatment, it was cooled and ball milled to a median particle size of 1 ± 0.5 μm. A certain amount of walnut shell-derived hard carbon was ground and mixed with an appropriate amount of sulfur powder and sodium hypophosphite in a mass ratio of 10:2:2. The mixture was placed in an inert gas-protected muffle furnace, heated to 300 ° C at a heating rate of 10 ° C per minute, kept warm for 1.5 hours, and naturally cooled to room temperature to obtain a phosphorus-sulfur co-doped hard carbon material. The nitrogen-phosphorus-sulfur co-doped hard carbon material was ground and dispersed in 500 mL of a 1M cobalt nitrate aqueous solution. After ultrasonication and stirring overnight, the precipitate was washed and centrifuged to remove it. After drying at 60°C for 12 hours, the material was placed in an inert gas-protected muffle furnace and heated to 1000°C at a rate of 10°C per minute, kept at that temperature for 0.5 hours, and then cooled naturally. After grinding and passing through a 500-mesh sieve, the final cobalt single-atom modified hard carbon material was obtained.
[0045] The hard carbon material in Example 1 was replaced by the hard carbon material in this example, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.
[0046] (Comparative Example 1)
[0047] The coconut shell was dried at 100°C for 5 hours, crushed and placed in a muffle furnace protected by inert gas, heated to 1200°C at a heating rate of 20°C per minute, and kept at this temperature for 2 hours for high temperature treatment. After high temperature treatment, it was cooled and ball milled to a median particle size of 2±0.5μm.
[0048] The hard carbon material in Example 1 was replaced by the hard carbon material in this example, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.
[0049] (Comparative Example 2)
[0050] The coconut shell was dried at 100°C for 5 hours, crushed and placed in a muffle furnace protected by inert gas, heated to 1200°C at a heating rate of 20°C per minute, and kept at this temperature for 2 hours for high temperature treatment. After high temperature treatment, it was cooled and ball milled to a median particle size of 2±0.5μm.
[0051] A certain amount of coconut shell-derived hard carbon was ground and mixed with an appropriate amount of urea in a mass ratio of 10:1. The mixture was placed in an inert gas-protected muffle furnace, heated to 600°C at a heating rate of 10°C per minute, kept at that temperature for 1 hour, and naturally cooled to room temperature to obtain a nitrogen-doped hard carbon material.
[0052] The hard carbon material in Example 1 was replaced by the hard carbon material in this example, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.
[0053] Table 1. Physicochemical properties of various examples
[0054] serial number D50(μm) Interlayer spacing (nm) <![CDATA[Specific surface area (m 2 / g)]]> Ash content (%) Moisture (%) Example 1 5.0±0.2 0.382 35.37 0.11 0.05 Example 2 1.0±0.2 0.371 10.29 0.16 0.05 Example 3 7.0±0.6 0.394 5.01 0.12 0.05 Example 4 2.0±0.5 0.368 29.32 0.11 0.05 Comparative Example 1 2.0±0.3 0.357 30.43 0.15 0.05 Comparative Example 2 2.0±0.3 0.354 31.33 0.12 0.05
[0055] Table 2. Performance characteristics of various examples and comparative examples
[0056]
[0057] In the above comparative examples, comparative example 1 is a blank example, and comparative example 2 is only subjected to non-metallic doping, and the comparison objects are all embodiment 1.
[0058] It can be seen from Table 1 that the specific surface area of each embodiment is greatly affected by the raw materials. Among the hard carbon material raw materials, the fiber content of the raw materials of Examples 1 to 3 and Comparative Examples 1 and 2 is relatively high, and they have more pores after roasting. Their specific surface area is significantly larger than that of Example 4 which uses starch as the raw material. If a larger specific surface area is desired, a hard shell material with a high fiber content should be used.
[0059] The final ash and moisture content of the products of each embodiment and comparative example are not much different, which are mainly affected by the roasting temperature.
[0060] It can be seen from Table 2 that compared with the blank test comparative example 1 and the comparative example 2 doped with only non-metal, various parameters such as the first-week coulombic efficiency, the first-week charging specific capacity, the capacity retention rate of 0.1C charge and discharge for 200 weeks, and the capacity retention rate of 0.3C charge and discharge for 200 weeks of each embodiment have been significantly improved, that is, when the negative electrode hard carbon material modified with single atomic points of metal elements is applied to sodium batteries, its various performances can be greatly improved.
[0061] By comparing the data of Example 3 with that of Example 4, it can be seen that the type of precursor and the type of metal doping source have a certain influence on the final data, but the overall influence is small.
[0062] Comparing the data of Examples 1 to 4, it can be seen that no matter what kind of biomass carbon source, precursor and metal element are used, the final performance of the sodium battery is not greatly affected.
[0063] Based on the above analysis, it can be seen that what ultimately affects the performance of sodium batteries is the single metal element modification action itself, which has a great impact on the surface microenvironment of the hard carbon material, and its overall sodium storage capacity is very excellent.
[0064] It should be understood that the present invention is described by some embodiments, and those skilled in the art will appreciate that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom, characterized in that The following steps are involved: S1: calcining the biomass carbon source under an inert atmosphere to obtain a hard carbon material; S2: crushing the hard carbon material in the previous step and grinding it with a non-metallic doping source to obtain a precursor-containing mixture; S3: sintering the precursor-containing mixture under an inert atmosphere to obtain a hard carbon material doped with non-metallic heteroatoms; S4: impregnating the non-metallic heteroatom-doped hard carbon material in a high-concentration metal salt solution, centrifugally drying, and then sintering in an inert atmosphere to obtain a sintered product; S5: The sintered product obtained in the above step is washed with an acid aqueous solution.
2. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: In the step S1, the calcination temperature is 1000-1500° C., and the calcination time is 2-10 hours.
3. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: The non-metal doped into the non-metallic doping source is nitrogen, phosphorus or sulfur, and the non-metallic doping source is one or more of urea, dicyandiamide, melamine, dopamine hydrochloride, thiourea, polyaniline, polypropylamine, polypyridine, polypyrrole, chitosan, sodium hypophosphite, sodium hypophosphite, ammonium dihydrogen phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, sodium sulfide nonahydrate, sublimated sulfur, and sodium dodecyl sulfate.
4. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: In the doping process of step S2, the material ratio of the hard carbon material to the non-metallic doping source is C:(N / P / S)=100:1-100:
25.
5. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: In the step S3, the sintering temperature is 300-800° C., and the sintering time is 0.5-5 hours.
6. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: The high concentration metal salt solution in step S4 is zinc nitrate, zinc chloride, zinc acetate, zinc sulfate, cupric chloride, copper nitrate, copper sulfate, cupric acetate, ferric chloride, ferric nitrate, potassium ferrocyanide, nickel chloride, nickel sulfate, cobalt nitrate, cobalt chloride, manganese chloride, manganese acetate, ammonium molybdate, sodium tungstate, ammonium metatungstate, vanadium trichloride, cadmium chloride, cadmium nitrate, chromium chloride, ammonium cerium nitrate, cerium nitrate, magnesium carbonate, magnesium chloride, magnesium acetate, calcium chloride, calcium sulfate, calcium carbonate, aluminum chloride, zirconium chloride or a mixture thereof, and its concentration range is 1 to 10 mol / L.
7. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: The sintering temperature in step S4 is 300-1000° C., and the processing time is 0.5-3 hours.
8. The method for preparing a negative electrode material for a sodium ion battery carrying a metal single atom according to claim 1, characterized in that: The acid used for washing in step S5 is hydrochloric acid, sulfuric acid, acetic acid or a mixture thereof, and the pH value thereof is controlled to be 0.1-1.
9. A sodium ion battery negative electrode material supporting a metal single atom, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing atomic-scale dispersed metal nitrogen-doped carbon material through secondary thermal dispersion
CN112687894A
Hard carbon negative electrode material and preparation method and application thereof
CN116706034A
Molybdenum-based doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN117658101A
Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material
CN118005004A
Biomass-based hard carbon active material, preparation thereof and application of biomass-based hard carbon active material in sodium-ion battery
CN118343733A
Cited By
Iron-selenium double-monatomic nitrogen-doped carbon-based composite material as well as preparation method and application thereof
CN120955099A
